Protein fraction from Artocarpus altilis pulp exhibits antioxidant properties and reverses anxiety behavior in adult zebrafish via the serotoninergic system. (March 2020) - Gonçalves, Nidyedja Goyanna Gomes; de Araújo, José Ismael Feitosa; Magalhães, Francisco Ernani Alves; Mendes, Francisco Rogênio Silva; Lobo, Marina Duarte Pinto; Moreira, Ana Cristina de Oliveira Monteiro; Moreira, Renato de Azevedo
Graphical abstract: Highlights: PFBp is a protein isolate from breadfruit with nutraceutical potential. PFBp contains high levels of essential amino acids. PFBp has metal-chelating activity. PFBp induces anxiolysis in zebrafish anxiety models via the serotoninergic system. Abstract: Breadfruit ( Artocarpus altilis ) is a staple food in tropical regions and has several uses. The aim of this study was to establish the nutraceutical potential of an enriched protein fraction of breadfruit pulp (PFBp). PFBp was characterized by Fourier transform infrared spectroscopy, electrophoresis, zymography, thin-layer chromatography, and mass spectrometry. PFBp toxicity was assessed in vitro and in vivo. Its pharmacological effects were determined using zebrafish anxiety models, open field test, and light/dark test. PFBp is rich in essential amino acids (49.59 g/100 g), predominantly lysine and leucine. It contains proteases, including cysteine proteases and three major proteins (20–30 kDa). PFBp was not cytotoxic and showed ion-chelating antioxidant activity. It induced anxiolysis in zebrafish anxiety models. This effect was mediated by the serotoninergic system, mainly, 5-HTR1A, 5-HTR2C, and 5-HTR3 . PFBp is a natural nutraceutical product. As a food supplement, PFBp could improve and sustain mental health.